2005
DOI: 10.3319/tao.2005.16.3.531(t)
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Well Log Study on the Paleoenvironment of the Hydrocarbon Producing Zones in the Erchungchi Formation, Hsinyin, SW Taiwan

Abstract: Gamma ray log facies of nine wells were used to reflect the vertical profile of grain size and were combined with well sample data to deduce the paleoenvironment of the Erchungchi "A" Member in the Hsinyin and Pachanchi areas. Four log facies were recognized in the studied intervals: a thick funnel-shaped facies representing a prograding delta; a thin funnelshaped facies representing a crevasse splay; a boxcar-shaped facies representing a distributary channel; a bell-shaped facies representing a fluvial or del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Selley, 1985;Cant, 1992;Posamentier and Allen, 1999;Chow et al 2005). This facies occurs within floodplain deposits and probably corresponds to fine-to medium-grained sandstone facies St and Sr (Table 1).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Selley, 1985;Cant, 1992;Posamentier and Allen, 1999;Chow et al 2005). This facies occurs within floodplain deposits and probably corresponds to fine-to medium-grained sandstone facies St and Sr (Table 1).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of claystone clasts or mud pebbles in a channel deposit will generate higher values on the gamma-ray log, even if the parent material is a 'clean' sandstone. Similarly, the presence of carbonaceous material will also act to increase the value of the gamma-ray log (Chow et al 2005).…”
Section: Factors Affecting Gamma-ray Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of modern sedimentary environments (Selley 1985;Amajor and Agbaire, 1989;Chow et al, 2005) revealed that vertical profiles of grain size from a specific environment have certain characteristics. For instance, prograding deltas and barrier bars deposit display an upward-coarsening grain size profiles (Fig.…”
Section: Description Of Gamma Ray Log Faciesmentioning
confidence: 99%